Speciation of the “darwinii Complex” (genus Liolaemus, “patch group”) in the southernmost area of its distribution (Reptilia: Tropiduridae) - Cei, José Miguel Alfredo María (1999)
A new species of the Liolaemus darwinii complex is reported and described, for the northern Chubut Province, Argentina, from the rocky southern slopes of the Somuncura plateau. It is the first case of speciation in this complex for the southernmost region of the very extensive distribution area of the its nominal species, which was however splitting in several other mainly allopatric taxa in the northwestern Argentine provinces, as reported in the results of a recent careful research.